The Prevalence of Headache Among Athletic University Students - Jahani, Pegah (Asian J Sports Med, 2016)
BACKGROUND: Headache is certainly one of the most common medical complaints of general population and one of the important causes of consumption of drugs. Despite its high overall prevalence, the epidemiology of exertional headache is not clear enough. OBJECTIVES: To determine the prevalence of headache in athletic and non-athletic university students and also estimating its variation between different sports fields including concussion prone sports. MATERIALS AND METHODS: This cross-sectional study comprised 739 subjects (367 athletes and 372 non-athletes). The present study was carried out on athletic and non-athletic university students aging between 18 to 28 years. An athlete was defined as a person who had at least one year of experience in sports including football, volleyball, basketball, wrestling, boxing, martial arts, track and field, chess, handball and swimming for three sessions a week each lasting at least 2 hours. The random selection of these participants was done by an independent statistical consultant. A questionnaire was used for data collection which was then analyzed by statistical methods. RESULTS: Our study comprised 739 subjects (367 athletes and 372 non-athletes). Among athletic university students, 152 (41.2%) participants complained of headache. Such a complaint was present in 217 (58.3%) non-athletic university students. This lower prevalence of headache in athletes was statistically significant (P value < 0.001). Among ten different sports fields, the prevalence of headache among wrestlers was significantly higher than others (P value < 0.001). CONCLUSIONS: The prevalence of headache is seemingly lower in athletic university students than non-athletic ones. In addition, among athletes, those who are participating in concussion prone sports especially wrestling experience headache more than athletes of other fields.